Financial Crisis and its Effect on Psychological Well-Being, Health, Satisfaction, and Financial Incapability; A Systematic Review - Paul Wesley Thompson (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Objectives: The decline in GDP caused by the global economic recession of 2008 and that caused by the COVID-19 pandemic has resulted in the poor economy of countries around the globe with increased rates of unemployment and adverse job conditions. This systematic review aims to identify the impact of a Financial crisis on Psychological well-being, Life satisfaction, Health Satisfaction, and Financial Incapability. Methodology: The literature included in the review was searched from Feb 1, 2023, to March 26, 2023, by using the PUBMED database as the search engine. Studies discussing the impact of the financial or economic crisis on psychological well-being, Health, Life satisfaction, and Financial Incapabilities published in the English Language were included in this review whereas systematic reviews and metanalysis, case reports, articles published in languages other than English and articles with limited access were excluded. Results: Of the 26 articles found eligible for the study, there were 22 Quantitative studies, 2 qualitative studies, and 2 Mixed Method Studies. Most of the articles included in this study discussed the Global Economic crisis caused by COVID-19 and the Global Financial Crisis of 2008. Almost 80% of the studies included in this review discussed psychological well-being and the prevalence of psychological disorders including Depression, Anxiety, Stress, Fear, Loneliness, Burnout, and Suicide whereas the rest of the articles discussed mortality regarding mental disorders. Conclusion: Financial crisis or economic recession results in an increased prevalence of common mental disorders affecting psychological well-being by increasing rates of unemployment and adverse job conditions. Policymakers with competitive financial behavior and knowledge are essential elements for psychological well-being and life satisfaction. Keywords: Economic Crisis, Indebtedness, Mental illness, Psychological well-being, Depression, Anxiety